Pengaruh Literasi Keuangan dan Sikap Keuangan Terhadap Perilaku Pengelolaan Keuangan Mahasiswa Prodi Pendidikan Ekonomi Undiksha - Rahayu, Ni Komang Dwi Savitri; Meitriana, Made Ary (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2023)
The purpose of this study was to explore whether financial literacy and financial attitudes influence financial management behavior. This study used causal quantitative research. The population of this study is 338 students of the Economic Education Study Program, Faculty of Economics, Undiksha. The total number of samples in this study was 184 people obtained by random sampling technique. The types of data used include quantitative data, secondary data sources, and document data collection. Multiple linear regression analysis is a data analysis technique used. The results showed that (1) Financial literacy has a positive effect on financial management behavior. (2) Financial attitudes have a significant positive effect on financial management behavior. (3) Financial management literacy and financial management attitudes simultaneously have a positive impact on financial management behavior. The higher a person's financial literacy and ability to apply financial aspects, the wiser his financial management behavior will be to be able to make the right decisions in making financial decisions. The higher the level of awareness of financial attitudes, the more decisions are taken in financial management to avoid financial problems.